Rehabilitation for Persistent Pain Across the Lifespan - Nijs, Jo; Ickmans, Kelly (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The area of rehabilitation research for patients having persistent pain is on the move. The rapid growth in pain science has inspired rehabilitation clinicians and researchers around the globe. This has led to breakthrough research and implementation of modern pain science in rehabilitation settings around the world. Still, our understanding of persistent pain continues to grow, not in the least because of fascinating discoveries from areas such as psychoneuroimmunology, exercise physiology, clinical psychology and nutritional (neuro)biology. This offers unique opportunities to further improve rehabilitation for patients with chronic pain across the lifespan. Also, the diversity of health care disciplines involved in the rehabilitation of chronic pain (e.g. physicians, psychologists, physiotherapists, occupational therapists, nurses, coaches) provides a framework for upgrading rehabilitation for chronic pain towards comprehensive lifestyle approaches.